Structural and biomechanical properties and trace elements composition of the corneoscleral eye shell in normal tension glaucoma - L. L. Arutyunyan; E. N. Iomdina; Yu. S. Morozova; S. I. Anisimov; S. Yu. Anisimova (Российский офтальмологический журнал)
The results of comparative studies of the structural and biomechanical features of the corneoscleral eye shell in various clinical forms of glaucoma are presented. The article discusses how the systemic and local imbalance of trace elements that regulate collagen biosynthesis, the formation of cross-links in the connective tissue structures of the sclera, and the hydrodynamics of the intraocular fluid, affect the intraocular pressure level, and thereby the character of the development of glaucomatous lesions in normal tension glaucoma. Modern literature is shown to indicate the prospects for further research in this direction.